Current process and outcomes of the surgical management of LUTS due to benign prostatic enlargement: how consistent are we? – results from the multi-institutional audit of surgical management of BPE (AuSuM BPE) in the United Kingdom. Issue 2 (May 2021) - Joshi, Hrishi; Sali, Gaurav; Paramore, Louise; Jones, Richard; Lazarowicz, Henry; Kujawa, Magda Lucia; Pandit, Amol; David, Rotimi; Wilson, Katherine; Bates, Christopher; Shergill, I; Gan, Christine; et al.
Objective: In view of changing landscape of surgical treatment for LUTS secondary to BPE, this audit was undertaken to assess key aspects of the processes and outcomes of the current interventional treatments for BPE, across different units in the UK. Materials and method: A multi-institutional snapshot audit was conducted for patients undergoing interventions for LUTS/BPE over 8-week period. Using Delphi process two-part proforma was designed to capture data. Results: 529 patients were included across 20 NHS trusts in England and Wales. Median age was 73 years. Indications for surgery were acute retention (47%) and LUTS (45%). 80% of patients had prior medical therapy. TURP formed the commonest procedure. 27% patients had <23 hour hospital stay. Immediate (21%) and delayed (18%) complications were Clavien-Dindo <2 category. High proportion of patients reported residual symptoms. Type and indication of surgery were significant predictor of complications, length of stay and failure of TWOC outcomes, on multivariate analyses. There were variations in departmental processes, 50% centres used PROMs. Conclusion: Monopolar TURP still remains the commonest intervention for BPE. Most departments are adopting newer technologies. The audit identified opportunities for development of consistent, effective and patient centric practices as well as need for large-scale focused studies.